KEPEMIMPINAN PENDIDIKAN MADRASAH SEBAGAI UPAYA PENINGKATAN KUALITAS PELAYANAN DALAM MANAJEMEN KEARSIPAN - Bimo Budhi Wahyu Syahfrudin; Kartiko Nur Hidayatulloh; Wafa Naufal Arifin; Siswadi (STKIP Subang, 2026)
This study aims to analyze the role of madrasah educational leadership in improving service quality through effective archival management. This research employs a library research approach by reviewing various scientific literature, books, and previous studies related to educational leadership, public service, and archival management. The findings indicate that madrasah leadership plays a strategic role in establishing an orderly, accountable, and technology-based archival system. Visionary, participatory, and transformational leadership can enhance administrative service quality through systematic, fast, and accurate archive management. In addition, the implementation of digital archiving and the strengthening of organizational culture are crucial factors in improving service quality. Therefore, madrasah educational leadership becomes a key factor in realizing effective archival management and improving the quality of educational services.